Non-chemical Control of Root Parasitic Weeds with Biochar - Eizenberg, Hanan; Plakhine, Dina; Ziadne, Hammam; Tsechansky, Ludmila; Graber, Ellen R. (Frontiers in Plant Science, 2017)
This study tested whether soil-applied biochar can impact the seed germination and attachment of root parasitic weeds. Three hypotheses were evaluated: (i) biochar adsorbs host-exuded signaling molecules; (ii) biochar activates plants’ innate system-wide defenses against invasion by the parasite; and (iii) biochar has a systemic influence on the amount of seed germination stimulant produced or released by the host plant. Three types of experiments were performed: (I) pot trials with tomato (Solanum lycopersicum) infested with Phelipanche aegyptiaca PERS. (Egyptian broomrape) and three different types of biochar at concentrations ranging from 0 to 1.5%, wherein tomato plant biomass, P. aegyptiaca biomass, and number of P. aegyptiaca-tomato root attachments were quantified; (II) split-root biochar/no-biochar experiments under hydrophonic growing conditions performed in polyethylene bags with tomato plant rootings, wherein P. aegyptiaca seed germination percentage and radicle attachment numbers were quantified; and (III) germination trials, wherein the effect of biochar adsorption of GR-24 (germination stimulant) on P. aegyptiaca seed germination was quantified. Addition of biochar to the pot soil (Experiment I) resulted in lower levels of P. aegyptiaca infection in the tomato plants, mainly through a decrease in the number of P. aegyptiaca attachments. This led to improved tomato plant growth. In Experiment II, P. aegyptiaca seed germination percentage decreased in the biochar-treated root zone as compared with the no-biochar control root zone; P. aegyptiaca radicle attachment numbers decreased accordingly. This experiment showed that biochar did not induce a systemic change in the activity of the stimulant molecules exuded by the tomato roots, toxicity to the radicles, or a change in the ability of the radicles to penetrate the tomato roots. The major cause for the decrease in germination percentage was physical adsorption of the stimulant molecule by the biochar (Experiment III). Adding biochar to soil to reduce infections by root parasitic weeds is an innovative means of control with the potential to become an important strategy both for non-chemical treatment of this family of pests, and enhancing the economic feasibility of the pyrolysis/biochar platform. This platform is often viewed as one of a handful of credible strategies for helping to mitigate climate change.